PENERAPAN TEKNIK PERMAINAN MALEN NACH WÖRTERN DALAM PEMBELAJARAN BAHASA JERMAN UNTUK MENINGKATKAN PENGUASAAN KOSAKATA - Masniari Hutagalung, Surya (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
This research is a classroom action research that uses two cycles. The purposes of this research are to describe the process of the implementation ofMalennachWörtern GamesTechniques in German Language Learning and to increase of students’ vocabulary mastery of the first semester students of German Language Education study program, the state university of Medan. The sample in this researchare 30 students ofthe first semester student German Language Education study program. The implementation ofMalennachWörtern GamesTechniques went smoothly, based on the scenario. Based on observations in the first cycle, the students may respond well and enthusiastic in implementingMalennachWörtern gametechniques. Theaverage ofpre-test resulting value was 60, while the average of final test was 70. Based on the evaluation and reflection on the first cycle, improvements occurred in the second cycle. The resulting value at the end of the second cycle test average was 85. Based on the value of the first cycle and the second cycle, it can be concluded that students increase their vocabulary mastery by using MalennachWörterngamestechniques.